Quaternary tracking of the Basin changes (Case Study: Ghezel Ozan) - Hassan Jafari; Fatemeh Bakhtiyari (تحقیقات کاربردی علوم جغرافیایی)
The Ghezel Ozan basin in an area of 50000 KM2 is in the northwest of Iran. Recognition of variables like captivity and deviation of rivers, erosion and compact surfaces, the affects of old lakes by the reflected affects on 1:50000 scaled topographic maps of the region, are some of the points which is tried to find out the changes of Quaternary of the basin. Although Ghezel Ozan basin is ended to Caspian sea as an open basin, the geomorphologic and topographic evidences show that this basin became independent between two basins of Ghom and Orumiye after Pasadenian moves and also was multiple closed sub basins which the waters were moved to the central pits in each surface such as Bijar, Zanjan, Tarom, Yangi Kand and Miyane. The size of some of these pits is such huge so that could be visible in topographic maps by water network and marl sediments of their bed. On the other hand, some are very small and limited which follow the local topographic position or has shaped under the influence of the main processes of the time and has been destroyed by changes. The past topographic situation and the main processes of glaciers in cold Quaternary, has made different lakes near Ghale Chay River. Pari Lake is an obvious example. However nowadays it is irrigated by an artificial channel ramified by Ghale Chay River.